Development and Fabrication of Carbon Nanotube (CNT)/CuO Nanocomposite for Volatile Organic Compounds (VOCs) Gas Sensor Application. Issue 1 (22nd December 2021) - Onthath, Haseena; Maurya, Muni Raj; Bykkam, Satish; Morsy, Hagar; Ibrahim, Muna; Ahmed, Alaa Elsafi; Riyaz, Najam‐US‐Sahar; Abuznad, Raghad; Alruwaili, Aeshah; Kumar, Bijandra; Abdullah, Aboubakr M.; Kasak, Peter; et al.
Abstract: Volatile organic compounds (VOCs) have been recognized as one of the primary trace segments of atmospheric air pollutants. The change in the level of VOCs in the surrounding environment can lead to chronic health issues, respiratory problems, nerve system disorder, and toxicity in kidneys/liver. Thus, monitoring of VOCs concentration in the surrounding environment is significant for avoiding serious health problems. Herein, copper oxide (CuO) nanoparticle and carbon nanotube (CNT) nanocomposite (NC) are presented for the efficient detection of VOCs. The scalable sol‐gel method is adopted for the controlled growth of CNT/CuO NC. The structural, elemental, and morphological analysis is performed by XRD, FTIR spectroscopy, and SEM characterization, respectively. The VOCs sensor was fabricated by drop‐casting the as‐synthesized CNT/CuO NC on interdigitated electrodes (IDEs). The CNT/CuO sensing response is analyzed for six VOCs that include toluene, methanol, acetone, chloroform, xylene, and benzene. The CNT/CuO response towards different VOCs is investigated with respect to change in resistance of the material in the presence of test VOC and in an inert atmosphere. In comparison to other VOCs, the sensor exhibits high sensitivity toward benzene. The estimated change in relative resistance (AR ) for benzene is ≈0.62% for 500 ppm concentration. Moreover, the sensor apprehended a detection of benzene with a concentration as low as 5 ppm. The as‐synthesized CNT/CuO NC offers high sensitivity and low detection limit, which benchmark its potential for benzene detection.